Burnout: Developmental Influences - Meyer, John H. (Canadian Journal of Counselling and Psychotherapy, 2012)
Burnout is a phenomenon of interest to many mental health professionals. It is a complex issue with no simple resolution. This study explored the origins of the phenomenon as perceived by twenty mental health professionals. It found that in some cases personal unresolved issues in the professional may be an important influence in the development of burnout. Organizational issues such as unrealistic pre-employment expectations, conflict between individual and organizational goals and structural difficulties within the organization were also implicated.